Beach handball European Championships analysis Zagreb 2017 - Zapardiel, J. C. (EHF Web Periodical, 2018)
The data collection for the quantitative analysis was carried out in situ by volunteers selected for this purpose. These volunteers received training a week before the start of the championship. This training was given by European Handball Federation staff. In each match, the volunteers were accompanied by a Federative Delegate who narrated the different actions that were being carried out. All collected data were transferred to a spreadsheet to be treated with the SPSS v.22 software afterwards. The normality of the dependent variables was checked by the asymmetry and kurtosis tests, resulting in normal variables. The contrasts of mean differences between gender and category variables were studied by means of multivariate analysis of covariance. When the variables did not show significant differences and their degree of association was close to zero, they were studied as a single group. The rest of the variables were studied as independent groups. Subsequently, a descriptive and inferential analysis among the variables of the study was carried out. In the inferential analysis, when the variance homogeneity test showed significance, the Welch test was used; when it did not show significance, the ANOVA test was used. In the inferential quantitative analysis, firstly, a comparison of the throws and saves was made based on the position of each team in the final ranking. The variables absolute category and under-17 were treated as a single group, since the covariance tests showed no significance and their degree of association was close to zero. In this way, the variables inflight shot, goalkeeper throw and 6-metre throw were treated. With this result, we increased the size of the sample and the analysis reached greater power. The variables one-point shot, spin shot, specialist throw and total throw were treated as independent variables, since the study of the covariance showed significance. Secondly, a comparison of the throws and saves was made based on the following grouping of the final classification: finalists, fourth finalists and eighth finalists. The data collection for the qualitative analysis was carried out a posteriori using the matches recorded by the organization during the championship. This qualitative analysis has not followed the criteria of scientific quality. Despite this, we decided to include it since we believed that this type of analysis could be a demand from potential readers of this type of work. Future investigations of this type of analysis should follow the criteria described in the work of Morillo, Reigal and Hernández-Mendo (2015).